Transformasi Pembelajaran Sekolah Dasar melalui Penerapan Pembelajaran Berbasis Teknologi di SDIT Al Qudwah - Dilla Desfrita Wahyuni; Ayumi Vesaka; Rika Novita; Erman Har; Karmila Suryani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The transformation of learning in elementary schools has become an important requirement in line with technological developments and changes in student characteristics. Technology-based learning is seen as one strategy to improve the quality of the learning process and outcomes. This study aims to describe and analyze the application of technology-based learning in transforming learning at SDIT Al Qudwah. The study uses a qualitative approach with a case study design. The research subjects included the principal, teachers, and students. Data collection techniques were conducted through in-depth interviews, observations, and documentation studies. Data analysis was carried out interactively through data reduction, data presentation, and conclusion drawing. The results show that the application of technology-based learning can encourage more interactive learning transformation, increase student engagement, and help teachers develop innovative learning strategies. In addition, technology-based learning also contributes to strengthening learning management and improving teachers' digital competencies. However, the application of technology-based learning still faces several challenges, such as limited infrastructure and differences in teachers' digital capabilities. This study concludes that technology-based learning plays an important role in transforming elementary school learning and needs to be continuously supported by school policies and teacher competency development.